USING PORTAL TECHNOLOGIES TO DEVELOP THE COMMON USER INTERFACE (CUI) - Lim, Edward (Malaysian Journal of Library and Information Science, 2000)
Describes the use of portal technologies currently used by e-commerce systems to provide common user interface to online library catalogues and other electronic information resources. The Monash University Library has developed a window client called Monalisa which allows access to networked CD-ROMs and other locally hosted databases from a single menu.